2008
DOI: 10.1007/s11325-008-0211-9
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial obesity in patients with obstructive sleep apnea

Abstract: Craniofacial obesity in the bucco-submandibular regions is associated with OSA and may provide valuable screening information for the identification of patients with undiagnosed OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…Full details of the sleep study for the same group of patients can be found elsewhere. 6,19 Table 1 shows the demographic profile of 120 subjects classified according to age and sex. The control group included 37 females and 23 males.…”
Section: Sleep Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Full details of the sleep study for the same group of patients can be found elsewhere. 6,19 Table 1 shows the demographic profile of 120 subjects classified according to age and sex. The control group included 37 females and 23 males.…”
Section: Sleep Studymentioning
confidence: 99%
“…5 Patients with OSA manifest a spectrum of craniofacial abnormalities and obesity that appear to promote upper airway obstruction during sleep. 6 The contributions of skeletal abnormalities vary among patients and between ethnic groups. For example, Asians have more pronounced skeletal abnormalities and are less obese than white subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Banabilh et al in [13] carry out an accurate analysis of the face shape, using the 3D stereophotogrammetry, in order to detect patients more prone to severe form of sleep apnea; hence, although this study is one of the first investigating the relations between 3D accurate facial data and specific healthy/unhealthy condition, it cannot be properly compared to our study, nor with respect to the methodology neither to the objective. Other works (such as by Coetzee et al [8] and Tinlin et al [9]) aim to assess the health status focusing on body fat; on the contrary, they measure the perceived fat adiposity, hence they do not provide a reproducible measure for the assessment of the health status.…”
Section: Discussionmentioning
confidence: 96%
“…Also, measurements and indexes derived from anthropometry may be used to monitor the nutritional status, and are currently studied to disclose existing relations with syndromes, as the obstructive sleep apnea, reported by Balabilh et al in [13]), and health risk factors, such as the cardiovascular or the cardio-metabolic risk, in [14] by Millar et al…”
Section: Standard Anthropometric Measurementsmentioning
confidence: 99%
See 1 more Smart Citation